2017
DOI: 10.7150/jca.19100
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Inhibits Cancer Stem Cells and Sensitizes to Chemo- and Photodynamic Therapy in Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is an Epstein-Barr virus-associated malignancy occurring at high incidence in Southeast Asia and southern China. In spite of the good response to radio- and chemo-therapy at the early stage, resistance and recurrence develop in NPC patients in the advanced setting. Cancer stem cells (CSCs) play an important role in drug resistance and cancer recurrence. Here we report that lovastatin, a natural compound and a lipophilic statin that has already been used in the clinic to treat hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…20 In fact, drug-resistant cell populations have more CSCs, 21,22 which are more resistant to conventional cancer therapies than the non-CSC subpopulation. 23 CSCs mediate patients' drug resistance through several different mechanisms. Studies of pancreatic cancer have revealed that there is a definite correlation between EMT-activated CSCs and tumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…20 In fact, drug-resistant cell populations have more CSCs, 21,22 which are more resistant to conventional cancer therapies than the non-CSC subpopulation. 23 CSCs mediate patients' drug resistance through several different mechanisms. Studies of pancreatic cancer have revealed that there is a definite correlation between EMT-activated CSCs and tumor drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol synthesis through the mevalonate pathway can be inhibited by statins, for which the molecular target is the enzyme 3-hydroxy-3-methylglutharyl-coenzyme A reductase (HMG-COAR). In fact, treatment with different statins decreased self-renewal and CSCs content in breast (Ginestier et al, 2012) and nasopharyngeal (Peng et al, 2017) carcinomas. Interestingly, similar effects were detected in CD133 + brain TICs (Wang et al, 2017a) where overexpression of mevalonate pathway genes was controlled by MYC, highlighting the variety of metabolic pathways controlled by the oncogene.…”
Section: Therapeutic Targeting Of Cscs Metabolismmentioning
confidence: 99%
“…The second group of lipid-lowering drugs, which have been proved to have anticancer properties are statins (i.e. Lovastatin) (Peng et al, 2017). The mechanism statins action involves the disruption of cholesterol biosynthesis, decrease of cell proliferation and survival (Martirosyan et al, 2010).…”
Section: Lipid Membranes As a Therapeutic Targetmentioning
confidence: 99%